Y si aprendo contigo? Interacciones entre parejas en el aula de matemáticas - César, Margarida (1998)
Social interactions, namely peer interactions, have been recognized as a facilitator factor for socio-cognitive development, knowledge aprehension, skills acquisition and school achievement. Contextualized studies showed that peer interaction is quite powerful when it is used in Maths classes. We will present the analysis of two cases from a research-action project (5th to 11th grade) which main goal is to promote peer interaction in the Maths class in order to implement pupils' socio-cognitive development, more positive attitudes towards Mathematics and their school achievement. The analysis of these cases underline the effectiveness of peer interaction according to the previous goals.